If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x+4x)=91
We move all terms to the left:
(3x+4x)-(91)=0
We add all the numbers together, and all the variables
(+7x)-91=0
We get rid of parentheses
7x-91=0
We move all terms containing x to the left, all other terms to the right
7x=91
x=91/7
x=13
| (J-6)=8h | | -2=3x-20÷4 | | -10(7n+2)=-10(9n+4) | | -8(t-4)-(t+8)=11 | | 7-5e=17 | | 1/3n-1/9=1/6n | | 60=15−5x | | (x-10)(3x+15)=300 | | 5-2(11+p)=1 | | 169=211-w | | 4x+3x-7=6x | | 75=-u+285 | | 60+4x=150+2x | | 8(b+7)=-24 | | 7t-6t-t+4t=12 | | 9m+4=27 | | 6x+7=28x-58 | | 10+2(y-3)=30 | | -0.9x=801 | | 1/4(8x+12)-x=14 | | 8q+12=-84 | | -14-4y=38 | | 169-y=224 | | -13+8+6x=40 | | 28=1/2(6x+8) | | 5c+3=C-12 | | 2+3x=8;2 | | 1/2(x-5)=-2x-5 | | -1=7q÷4 | | 13x-60=90 | | 12j+j-4j=18 | | 5c+3=-12 |